The roles of formic acid and levulinic acid on the formation and growth of carbonaceous spheres by hydrothermal carbonization. Issue 104 (27th October 2016) - Qi, Yujie; Song, Biying; Qi, Yang
Abstract : The roles of formic acid and levulinic acid on the formation and growth of carbonaceous spheres. Abstract : The catalytic conversion of biomass into 5-hydroxymethylfurfural (HMF) and acid has been investigated. However, until now there has been little mechanism research on the roles of acids produced during the process of hydrothermal carbonization of biomass on the formation and growth of carbonaceous spheres. In this work, we specifically demonstrate how the formic acid and levulinic acid molecules participate in the formation and growth of carbonaceous spheres by analyzing the size variations of solid products obtained from the four solution systems. The formic acid molecules play a critical role in catalytic conversion of fructose into HMF, which promotes the growth of carbonaceous spheres considerably. The primary function of levulinic acid molecules is taking part in the growth as building units and slowing the growth by reducing the surface density of hydroxyl groups of carbonaceous spheres. In addition, the levulinic acids molecules existed in solutions also promote the conversion from fructose to HMF to a certain extent.